1986
DOI: 10.1111/j.1600-0404.1986.tb07862.x
|View full text |Cite
|
Sign up to set email alerts
|

Passage of 5'-dFUrd and its metabolites 5-FU and 5-FUH2to CSF in a clinical Phase 1 study

Abstract: Lumbar puncture was performed on eight patients in a clinical Phase 1 study of doxifluridine (5'-dFDrd). 5'-dFUrd, 5'FU, and 5-FUH2 were shown to cross the blood-brain barrier to CSF. The maximal concentrations of 5'-dFUrd and 5-FUH2 were about 1-3% of the maximal concentrations in plasma, and were reached within 1-4 h after the end of iv infusion of 5'-dFUrd. 5-FUH2 showed a marked increase in CSF between 3 and 4 h to about 40-60% of the maximal plasma concentration in 5 of the patients, indicating a possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…Combining the in vitro unbound fraction in blood and brain homogenate, both K p,uu,brain and K p,uu,CSF were calculated to be 0.03 and 0.25 for capecitabine and 0.13 and 0.29 for 5-FU, respectively ( Table 2). The brain penetration of 5-FU in our study was comparable to the studies conducted by Bourke et al (1973) (K p,brain = 0.09 and K p,CSF = 0.43 in primates after IV injection of 5-FU-2-14 C), Kerr et al (1984) (K p,CSF = 0.11-0.48 in monkey after IV injection of 5-FU), and Heier et al (1986) (K p,CSF = 0.015-0.06 in human after IV injection of 59-DFUR). These data suggested that capecitabine and 5-FU had very poor brain penetration and low CSF penetration.…”
Section: Downloaded Fromsupporting
confidence: 79%
“…Combining the in vitro unbound fraction in blood and brain homogenate, both K p,uu,brain and K p,uu,CSF were calculated to be 0.03 and 0.25 for capecitabine and 0.13 and 0.29 for 5-FU, respectively ( Table 2). The brain penetration of 5-FU in our study was comparable to the studies conducted by Bourke et al (1973) (K p,brain = 0.09 and K p,CSF = 0.43 in primates after IV injection of 5-FU-2-14 C), Kerr et al (1984) (K p,CSF = 0.11-0.48 in monkey after IV injection of 5-FU), and Heier et al (1986) (K p,CSF = 0.015-0.06 in human after IV injection of 59-DFUR). These data suggested that capecitabine and 5-FU had very poor brain penetration and low CSF penetration.…”
Section: Downloaded Fromsupporting
confidence: 79%
“…Several studies have demonstrated subtle hippocampal damage to often give rise to explicit memory deficits [5][6][7][8][9]. Chemotherapeutic agent such as fluorouracil which is commonly used for breast cancer, penetrate the blood brain barrier [10] and may inhibit neurogenesis in the hippocampus. We hypothesized that adjuvant chemotherapy might damage the hippocampus and result in memory impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Both of these metabolites were shown to cross the blood-brain barrier in a Phase I study. 23 Since the 5′-DFUR molecule consists of a pentose sugar attached to fluorouracil, 5′-DFUR crosses the blood-brain barrier more easily than fluorouracil itself. 24 Capecitabine may cross the blood-brain barrier via the human concentrative nucleoside transporter in the form of 5′-DFUR, which was converted to fluorouracil due to the high concentration of thymidine phosphorylase in brain cells.…”
Section: Discussionmentioning
confidence: 99%